Ubudiyah practices and the usage of communication channels at Yayasan Daarut Tauhiid (DT), Bandung Indonesia: An exploratory study - Omar, Nuredayu; Mustaffa, Che Su (Global Academic Excellence, 2017)
Understanding Islamic management principles could help to develop a more appropriate type of management best practice in Islamic countries while still benefiting from the transfer of relevant Western management techniques and Western technology.Thus, this paper discussed the results of the exploratory study conducted at Yayasan Daarut Tauhiid (DT), Bandung Indonesia.This study utilized interviews and participative observation methods in order to explore the practice of Ubudiyah and the use of communication channels in conveying messages related to Ubudiyah.Ubudiyah or reliance on Allah is an element in the Islamic management - Islam as a whole, which includes the management of self, family, or organization.The findings revealed that DT implements the principle of Ubudiyah as the main basis in the management of their Islamic missionary, schools, businesses, and social responsibilities.The principle of Ubudiyah comprises the elements of Confident with Allah, Trust in Allah, and Sincere in Allah have been found emerged in this study. This study identified that DT has fully utilized communication channels such as printed advertising and collateral advertising, social media - Facebook, Twitter and Instagram, and WOM in communicating about Ubudiyah, the Islamic missionary, and their businesses. Each communication channel is meant to extend to different target audiences, but the main view in all messages must be based on Ubudiyah or reliance on Allah.The study also found that DT has been successful in their mission to embed Ubudiyah and communicate about it in their management and daily routines.This article has identify key issues for Islamic management implementation in developing an understanding of Islamic management systems.The paper also contributes to the sparse literature on Islamic management and communication.